Integrated process and control modelling of water recirculation in once-through boilers during low load and transient operation - Rosslee, Pieter (Department of Mechanical Engineering, 2021)
Power plant stability at lower loads is becoming ever more important, highlighting the increasing requirement for the development of advanced models and tools to analyse and design systems. Such tools enable a better understanding of the thermo-fluid processes and their dynamics, which improves the ability to specify and design better control algorithms and systems. During low load operation and transients, such as start-up and shutdown, the required water flow rate through the evaporator tubes of once-though boilers must be significantly higher than the evaporation rate to protect against overheating of the tubes until once-through operation is reached. Controlling the minimum required water flow rate through the evaporator and economiser is notoriously difficult. Within industry, strong emphasis is placed on maintaining the minimum required flow through the economiser and evaporator without adequate consideration of the potential thermal fatigue damage on the economiser, evaporator and superheater components and the risk of turbine quenching incidents. The purpose of this study was to develop an integrated process and control model that can be used to study transient events. The model developed in Flownex can simulate the complex thermo-fluid processes and associated controls of the feedwater start-up system. This includes the waterrecirculation loop, and allows for detailed transient analysis of the complete integrated system. The model was validated using data from an actual power plant in steady state as well as a transient cold start-up, up to once-through operation. Transient results from the model are also compared to the power plant unit during start-up for the addition or loss of mills using the existing control strategy. The model results compare well with the actual process behaviour. A new control strategy was then proposed and tested using the model. The results indicated significant improvement in control performance and overall controllability of the start-up system, and the large temperature fluctuations currently experienced at the economiser inlet during transients were significantly reduced. The new control strategy was also implemented on a real power plant unit undergoing commissioning. During all modes of start-ups (cold, warm and hot), as well as transients, the performance of the control system showed significant improvement, with a notable decline in instabilities of the feedwater flow. As predicted in the model, the large temperature fluctuations are significantly reduced. The new model therefore enabled the development of an improved control strategy that reduces damaging thermal fatigue. The general controllability of transients is also significantly improved, thereby minimizing risks of water carry-over, quenching and unit trips during start-up.